Occupational dose assessment of 64Cu-ATSM in a veterinary setting - Hetrick, Lucas, author; Johnson, Thomas, advisor; Kraft, Susan, committee member; Biller, Barbara, committee member (Colorado State University. Libraries, 2014)
64Cu-ATSM is an emerging radiopharmaceutical for diagnostic use in Positron Emission Tomography (PET) and has potential utility for radiation therapy but to date there are no studies that assess the occupational doses delivered to workers in either a hospital or veterinary environment. This study consisted of canine patients that were recruited at the Colorado State University James L. Voss Veterinary Teaching Hospital (VTH). The study was aimed at determining the radiation dose to veterinary workers from clinical PET/CT procedures using 64Cu-ATSM. To determine the dose to the workers, each worker was assigned two Electronic Personal Dosimeters (EPDs) to be worn on the chest and waist during the entirety of each procedure. The workers monitored during this study involved included a radiobiologist, a nuclear medicine technician, an anesthesiologist, and a veterinary surgeon. Seven canine patients were imaged over a ten month period with an average mass of 33.7 kg (a range of 20.0 - 55.1 kg) with an average injected activity of 5 MBq kg-1. The dose range for the radiobiologist was 2 -17 µSv, for the nuclear medicine technician 0 -14 µSv, for the anesthesiologist 0 - 12 µSv, and for the surgeon 0 -10 µSv. In a comparison between the results of this study and published literature on occupational exposures from human/veterinary FDG PET/CT procedures, 64Cu-ATSM veterinary PET/CT procedures, on a per patient bias, exposed workers to less radiation.
Keywords: 64Cu-ATSM; veterinary; radiation; occupational exposure